The Implementation of Rally Coach Strategy in Teaching Reading Comprehension: A Quasi Experimental Research - Syarifah Ulfiah; Samhudi Samhudi; Fadhlur Rahman (Journal of English Language and Pedagogy (JELPA), 2024)
Students’ comprehension of narrative texts was hampered in the chosen educational setting, necessitating the implementation of effective interventions. The Rally Coach strategy, an emerging approach, is based on the notion that collaborative learning boosts student performance. This study aims to determine if there is a significant difference in reading comprehension achievement between students taught using the Rally Coach Strategy and those taught using traditional methods. A quasi-experimental research design was employed to assess the efficacy of Spencer Kagan's Rally Coach Strategy in improving students' reading comprehension skills. The study's t-test results showed a significant improvement in reading comprehension, with a value of 6.039 exceeding the t-table result of 2.048, indicating a substantial improvement in reading comprehension achievement. These findings support the alternative hypothesis, implying that implementing the Rally Coach Method in the experimental classroom would significantly improve the quality of reading comprehension instruction. Overall, this study adds valuable empirical evidence to support the Rally Coach strategy's effectiveness in improving students' reading comprehension skills. This study addresses a critical educational concern by identifying a successful intervention to address low reading comprehension achievement and emphasizes the importance of cooperative learning strategies, such as the Rally Coach Strategy, in improving students' overall reading comprehension abilities.